An investigation into the fertilizer particle dynamics off-the-disc - Antille, Diogenes Luis; Gallar, Luis; Miller, P. C. H.; Godwin, R. J. (American Society of Agricultural and Biological Engineers, 2015)
The particle size range specifications for two biosolids-derived organomineral fertilizers (OMF) known as OMF10 (10:4:4) and OMF15 (15:4:4) were established. Such specifications will enable field application of OMF with spinning disc systems using conventional tramlines spacing. A theoretical model was developed, which predicts the trajectory of individual fertilizer particles off-the-disc. The drag coefficient (Cd) was estimated for small time steps (10-6 s) in the trajectory of the particle as a function of the Reynolds number. For the range of initial velocities (20 to 40 m s-1), release angles (0° to 10°) and particle densities (1000 to 2000 kg m-3) investigated, the analysis showed that OMF10 and OMF15 need to have particle diameters between 1.10 and 5.80 mm, and between 1.05 and 5.50 mm, respectively, to provide similar spreading performance to urea with particle size range of 1.00 to 5.25 mm in diameter. OMF10 and OMF15 should have 80% (by weight) of particles between 2.65 and 4.30 mm, and between 2.55 and 4.10 mm, respectively. Due to the physical properties of the material, disc designs and settings that enable working at a specified bout width by providing a small upward particle trajectory angle (e.g., 10°) are preferred to high rotational velocities. However, field application of OMF with spinning discs applicators may be restricted to tramlines spaced at a maximum of 24 m; particularly, when some degree of overlapping is required between two adjacent bouts. The performance of granular fertilizers can be predicted based on properties of the material, such as particle density and size range, using the contour plots developed in this study.
Keywords: Biosolids granules; Fertilizer particle trajectory; Fertilizer spreading; Landing distance; Organomineral fertilizers (OMF); Particle density; Particle diameter; Urea